English language teachers’ online community of practice during the Ukrainian refugee crisis: A thematic analysis of Facebook group discussions - Nosidlak, Katarzyna; Wolanin, Agata (Przegląd Wschodnioeuropejski, 2026)
The Russian invasion of Ukraine in February 2022 resulted in a sudden influx of refugee learners into Polish schools, placing teachers under significant pedagogical and emotional pressure. This study examines how Polish teachers of English as a foreign language (EFL) sought support and articulated professional challenges within a virtual community of practice, using a Facebook group as their platform, during this crisis. The analysis is based on 67 Facebook posts and 838 comments published between February 2022 and September 2023 in the largest EFL teachers’ Facebook group. Using thematic analysis, the study identifies key challenges related to the emotional burden, language barriers, assessment, and curriculum adaptation. The findings show that this virtual community fulfilled core functions of a community of practice, including problem solving, experience sharing, and emotional reassurance, compensating for limited institutional guidance.